Comparison of bleeding risk and hypofibrinogenemia-associated risk factors between tigecycline with cefoperazone/sulbactam therapy and other tigecycline-based combination therapies - Zhang, Lei; Cai, Xinfeng; Peng, Fangchen; Tian, Shuangshuang; Wu, Xinjing; Li, Yun; Guo, Jinlin (Frontiers in Pharmacology, 2023)
Background: Tigecycline and cefoperazone/sulbactam can cause coagulation disorders; tigecycline may also lead to hypofibrinogenemia, raising safety concerns. This study aimed to investigate whether tigecycline plus cefoperazone/sulbactam increases the risk of bleeding compared with other tigecycline-based combination therapies and identify risk factors for tigecycline-associated hypofibrinogenemia. Methods: In this multi-method, multicenter, retrospective study, coagulation and other baseline variables were compared using a cohort study, and risk factors for hypofibrinogenemia using a case-control study. Results: The 451 enrolled participants were divided into three group: tigecycline plus cefoperazone/sulbactam (Group A, 193 patients), tigecycline plus carbapenems (Group B, 200 patients) and tigecycline plus β-lactams without N-methylthio-tetrazole (NMTT) side chains (Group C, 58 patients). Activated partial thromboplastin time and prothrombin time were prolonged, and fibrinogen declined for all patients after tigecycline-based medication (all P<0.05). Prothrombin time in Group B was significantly longer than in other groups (P<0.05), but there were no significant differences in bleeding events between the three groups (P=0.845). Age greater than 80 years (OR: 2.85, 95% CI: 1.07 7.60), treatment duration (OR: 1.29, 95% CI: 1.19 1.41), daily dose (OR: 2.6, 95% CI: 1.29 5.25), total bilirubin (OR: 1.01, 95% CI: 1.01 1.02) and basal fibrinogen (OR: 1.32, 95% CI: 1.14 1.63) were independent risk factors of hypofibrinogenemia. The optimal cut-off for treatment course was 6 days for high-dose and 11 days for low-dose. Conclusion: Tigecycline plus cefoperazone/sulbactam didn’t increase the risk of bleeding compared with tigecycline plus carbapenem, or tigecycline plus β-lactam antibiotics without NMTT-side-chains. Coagulation function should be closely monitored in patients receiving tigecycline treatment.